2018
DOI: 10.1002/ffj.3439
|View full text |Cite
|
Sign up to set email alerts
|

Volatome analysis approach for the taxonomic classification of tree exudate collection using Proton Transfer Reaction Time of Flight Mass Spectrometry

Abstract: Natural resins exude from trees as viscous liquids, which subsequently harden by evaporation and/or oxidation. Their compositions and textures are complex and vary during the solidification processes, producing a typical volatile fragrant fraction. Many techniques have been applied to the study of resins in order to obtain considerable chemical information but no exploratory work has been conducted using Proton Transfer Reaction Time of Flight Mass Spectrometry (PTR‐ToF‐MS). For this reason its potential to ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 83 publications
(125 reference statements)
0
4
0
Order By: Relevance
“…A total of 129 and 130 VOCs were detected at five and nine days, respectively, in the range of measured masses (mass protonated range m / z = 20–300) after the subtraction of peaks associated with the PTR-MS ion source and their isotopes. VOCs’ putative identification is reported in Supplementary Table S2 [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Overall, all samples’ released VOCs were blends composed of similar compounds, but in different proportions.…”
Section: Resultsmentioning
confidence: 99%
“…A total of 129 and 130 VOCs were detected at five and nine days, respectively, in the range of measured masses (mass protonated range m / z = 20–300) after the subtraction of peaks associated with the PTR-MS ion source and their isotopes. VOCs’ putative identification is reported in Supplementary Table S2 [ 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 ]. Overall, all samples’ released VOCs were blends composed of similar compounds, but in different proportions.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the volatile profile analysis of each essential oil was performed with PTR‐ToF‐MS, a powerful instrument able to screen the entire VOC profile, with short response times, high mass resolution and virtually without an upper mass limit . A total of 142 different volatile compounds was identified by VOC analysis of the twelve essential oils extracted from plant resins.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, extraction was performed using the hydrodistillation method with water as the solvent. A commercial PTR‐MS 8000 (Ionicon Analytik, Innsbruck, Austria) instrument, which is useful for achieving the whole mass spectra from several matrices, was used to assess the volatile profile for the collection of different essential oil samples. The advantages and disadvantages of this tool, as well as the details of its operation are reported in Blake et al and Taiti et al The analysis was carried out following a similar methodology previously reported by Taiti et al Briefly, a glass vial (15 ml) containing 2 µl of oil sample was placed in a glass jar (3/4 L) and covered with glass lid fitted with two holes.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, methods of distinguishing different resins have been developed simultaneously. Taiti et al used proton transfer reaction time-of-flight mass spectrometry (PTR-ToF-MS) to classify different resins based on their volatile organic compound emission profiles [ 61 ]. Wei et al established a rapid and nondestructive method for identification of six resins by near-infrared reflectance spectroscopy (NIR).…”
Section: Quality Controlmentioning
confidence: 99%